2022
DOI: 10.3390/jpm12030408
|View full text |Cite
|
Sign up to set email alerts
|

Pericapsular Nerve Group (PENG) Block versus Supra-Inguinal Fascia Iliaca Compartment Block for Total Hip Arthroplasty: A Randomized Clinical Trial

Abstract: This study compared the effects of the pericapsular nerve group (PENG) block and supra-inguinal fascia iliaca compartment block (FICB) on postoperative analgesia and quadriceps strength following total hip arthroplasty under general anesthesia. A total of 58 patients were randomized to receive either PENG block (PENG group) or supra-inguinal FICB (FICB group) following anesthetic induction. The primary outcomes were the postoperative pain scores. Patients were randomized to receive either PENG block or supra-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 29 publications
2
96
2
Order By: Relevance
“…Based on the Cochrane risk of the bias assessment tool, the quality of the included studies ranged from low to high quality with seven studies of low quality [15][16][17][18][19][20][21]; two of moderate quality [22,23]; and six high-quality studies [24][25][26][27][28][29]. Risk of bias graph and summary of quality assessment domains of included studies are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Cochrane risk of the bias assessment tool, the quality of the included studies ranged from low to high quality with seven studies of low quality [15][16][17][18][19][20][21]; two of moderate quality [22,23]; and six high-quality studies [24][25][26][27][28][29]. Risk of bias graph and summary of quality assessment domains of included studies are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Among clinical studies utilizing PENG block ( n = 29), most are low-quality case reports/series [ 1 , 2 , 3 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], but one cohort study [ 59 ] and eight randomized controlled trials [ 4 , 5 , 60 , 61 , 62 , 63 , 64 , 65 ] appeared in the literature after late 2020. Definite post-procedural quadriceps weakness after PENG block was reported in two case reports [ 2 , 3 ] and two RCTs [ 4 , 5 ] (group A).…”
Section: Resultsmentioning
confidence: 99%
“…Definite post-procedural quadriceps weakness after PENG block was reported in two case reports [ 2 , 3 ] and two RCTs [ 4 , 5 ] (group A). Among PENG block studies that reported no post-procedural quadriceps weakness or made no mention of motor function at all, clinical manifestations of extra-IP spread of local anesthetics either as observed injectate spread to the FIC in ultrasound images [ 42 ], sensory loss of dermatomes corresponding to the femoral nerve [ 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ], or an absence of statistically significant difference in quadriceps strength in patients receiving a supra-inguinal fascia iliaca compartment block (SI-FICB) [ 60 , 61 ] were found in nine case reports/series [ 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ] and two RCTs [ 60 , 61 ] (group B). Nine case reports/series [ 1 , 48 , 52 , 54 , 55 , 56 , 57 , 64 , 66 ], one cohort study [ 60 ], and four RCTs [ 62 , 63 , 64 , 65 ] using PENG block specifically reported no motor block at all (group C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations